1989
DOI: 10.1073/pnas.86.20.7663
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-enhanced polymer degradation and release of incorporated substances.

Abstract: The effect ofultrasound on the degradation of polymers and the release rate of incorporated molecules within those polymers was examined. Up to 5-fold reversible increases in degradation rate and up to 20-fold reversible increases in release rate of incorporated molecules were observed with biodegradable polyanhydrides, polyglycolides, and polylactides. Up to 10-fold reversible increases in release rate of incorporated molecules within nonerodible ethylene/vinyl acetate copolymer were also observed. The releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(187 citation statements)
references
References 15 publications
4
183
0
Order By: Relevance
“…Then timed drug release could by activated by transdermal ultrasound. Polymers in a depot can be degraded by ultrasound [27,149], but this is a fairly slow process, and the same physicochemical mechanisms that degrade the polymers may degrade the proteins in the depot. What is needed is technology that will open and close the depot to protein transport.…”
Section: Needs In Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Then timed drug release could by activated by transdermal ultrasound. Polymers in a depot can be degraded by ultrasound [27,149], but this is a fairly slow process, and the same physicochemical mechanisms that degrade the polymers may degrade the proteins in the depot. What is needed is technology that will open and close the depot to protein transport.…”
Section: Needs In Proteinmentioning
confidence: 99%
“…It is well known that low frequency high intensity ultrasound (conditions promoting collapse cavitation) reduce the molecular weight of soluble polymers [26][27][28]. Polymer chain scission is attributed to viscous shear stresses that pull the backbone apart and to the generation of free radicals that may react with and break the chain.…”
Section: Perturbation Of the Drug Carriermentioning
confidence: 99%
“…It has been found out that ultrasonic can induce chemical bonds in polymers breaking [20]. For this study, when the samples are exposed to ultrasonic a part of hydroxyl groups may break away from the SU-8 backbones, as shown in Fig.…”
Section: Mechanism Of Ultrasonic Effect On Su-8 Swellingmentioning
confidence: 99%
“…4) when ultrasound was applied in continuous mode. Kost et al (1989) reported no difference between normal and sonicated histologic sections of rat tissue to 5 W/cm 2 (20 kHz, pulsed mode, 1 hr). This examination was performed on animal skin immediately after the experiment.…”
Section: In Vivo Experimentsmentioning
confidence: 99%